Structure, floristic and diversity from Laguna de San Diego (Samaná, Colombia) - Julio Andrés Sierra-Giraldo; Susana Velásquez-Franco; Mitchell James Power; Jairo Andrés Orozco-Agudelo; Luz Amparo Triana-Moreno (Rodriguésia)
Abstract The Magdalena Valley along the eastern slopes of the Central Andes in Colombia is characterized by both high biodiversity and endemism and human infrastructure development. In this study, we present the first botanical record from Distrito de Manejo Integrado Laguna de San Diego flora’s, part of South America’s northernmost active volcanic field. Here, we analyzed the diversity, structure, and composition in four different cover types (Dense forest: Bd, Mosaic of pastures with natural spaces: Mpen, Pastures: P, and Secondary vegetation: Vs). A total of 100 species and 42 botanical families were recorded. In Bd, the species with the highest IVI was Pourouma bicolor (20.9), while in the Mpen, was Triplaris dugandii (53.7); Psidium guajava (75.6) in P, and Guatteria punctata (21.2) in Vs. Bd exhibited the highest values of diversity across all measures (0D, 1D, and 2D). We strongly advocate for increased efforts to enhance the protection status and safeguard local species to protect biodiversity. This research adds to baseline botanical knowledge and should be used to minimize impacts of ecotourism, and the potential for future mining exploitation in biodiverse landscapes.